2015
DOI: 10.1371/journal.pone.0133678
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Exchange Rate of Bitcoin

Abstract: Bitcoin, the first electronic payment system, is becoming a popular currency. We provide a statistical analysis of the log-returns of the exchange rate of Bitcoin versus the United States Dollar. Fifteen of the most popular parametric distributions in finance are fitted to the log-returns. The generalized hyperbolic distribution is shown to give the best fit. Predictions are given for future values of the exchange rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 59 publications
0
98
0
1
Order By: Relevance
“…The question arises which parametric distribution can characterize the Bitcoin exchange rate. In Chu et al (2015), it is shown that the generalized hyperbolic distribution gives the best maximum-likelihood fit among a large set of parametric distributions. In Osterrieder (2017), the author shows that the asymmetric Student's t-distribution is the best descriptor for the returns of the most important cryptocurrencies, choosing from a reasonably large set of heavytailed distributions.…”
Section: Motivation and Normal Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question arises which parametric distribution can characterize the Bitcoin exchange rate. In Chu et al (2015), it is shown that the generalized hyperbolic distribution gives the best maximum-likelihood fit among a large set of parametric distributions. In Osterrieder (2017), the author shows that the asymmetric Student's t-distribution is the best descriptor for the returns of the most important cryptocurrencies, choosing from a reasonably large set of heavytailed distributions.…”
Section: Motivation and Normal Distributionmentioning
confidence: 99%
“…For a discussion of the normal distribution of exchange rates, see Coppes (1995). Corlu and Corlu (2015) and Chu et al (2015) discuss parametric approaches to modeling exchange rate returns. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Short and long term links are found, and Bitcoin is shown to exhibit the properties of both standard financial assets but also speculative assets, which fuel further discussion on whether Bitcoin should be classed as a currency, asset or an investment vehicle. Chu et al (2015) give the first statistical analysis of the exchange rate of Bitcoin. They fit fifteen of the most common distributions used in finance to the log returns of the exchange rate of Bitcoin versus the U.S. Dollar.…”
Section: Introductionmentioning
confidence: 99%
“…[4] fitted the Student's t, asymmetric Student's t, hyperbolic, generalized hyperbolic, generalized Lambda, skew t, normal inverse Gaussian and normal distributions to the data. [2] has fitted both heavy tailed and light-tailed distributions to the Bitcoin exchange rate: The normal, logistic, Laplace, exponential power, skew normal, skewed exponential power and asymmetric exponential power distributions have light tails. The Student's t, skew t, generalized t, skewed Student's t, asymmetric Student's t, normal inverse gamma, hyperbolic and generalized hyperbolic distributions have heavy tails.…”
Section: Heavy-tailed Distributionsmentioning
confidence: 99%
“…Some of the papers are: [3,4,5,6,7,8,9,10,11,12,13]. Probably the most comprehensive collection of distributions used to analyze any exchange rate data set is given by [2]. Each distribution was fitted by the method of maximum likelihood.…”
Section: Heavy-tailed Distributionsmentioning
confidence: 99%